(untitled) (Boletín Epidemiológico Semanal, 2023)
Introduction: This report provides information on invasive Haemophilus influenzae disease (IHD) in Spain for the years 2021-2022. Method: Descriptive epidemiological analysis of cases of IHD reported to the National Epidemiological Surveillance Network, years 2021 and 2022. The variables analysed were: sex, age, date of symptom onset, place of residence, death and serotype of the pathogen. Results: In 2021 there was a sharp decrease in incidence rate (IR), while in 2022 there was an increase in IR reaching the figure of pre-pandemic years. In 2021, 179 cases of IHD were reported with IR of 0.40. In 2022, a total of 462 cases were reported (IR of 0.97). The highest IR in 2021 and 2022 was observed in children under 1 year, IR of 5.05 and IR of 8.20, respectively. In 2022, the two youngest age groups (under 1 year of age and 1 to 4 years old) had a higher IR than observed in pre-pandemic years. The serotype of most of the cases of IHD that caused this increase is unknown. Conclusions: During 2021 there was a decrease in TI compared to the previous year (2020). In 2022, pre-pandemic TIs recovered. A high percentage of cases with unknown basic variables have been reported. Complete microbiological characterisation data are essential for disease surveillance.